2020
DOI: 10.1186/s12950-020-00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Anatabine ameliorates intestinal inflammation and reduces the production of pro-inflammatory factors in a dextran sulfate sodium mouse model of colitis

Abstract: Background: Inflammatory bowel disease (IBD) is the collective term for chronic immune-mediated diseases of unknown, multifactorial etiology, arising from the interplay between genetic and environmental factors and including two main disease manifestations: ulcerative colitis (UC) and Crohn's disease. In the last few decades, naturally occurring alkaloids have gained interest because of their substantial anti-inflammatory effects in several animal models of disease. Studies on mouse models of IBD have demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…On the other hand, the administration route of nicotine in vivo models (i.e., oral administration, subcutaneous injection) plays a crucial role in the potential antiinflammatory effects of nicotine in intestinal inflammation (AlSharari et al, 2013) therefore we might have not been able to capture the full potential of nicotine with our model as nicotine dissemination through the blood stream, intestinal absorption, or gastrointestinal metabolism might play a crucial role in nicotine bioavailability and anti-inflammatory effects in the gut. Of note, other minor tobacco alkaloids, nAChR agonists as well, were also suggested as having potential antiinflammatory effects (Olsson et al, 1993;Bai et al, 2007;Alijevic et al, 2020;Ruiz Castro et al, 2020). Among these, the alkaloids anatabine and cotinine have displayed protective effects in animal models of inflammatory conditions, including Alzheimer's disease (Paris et al, 2011), Parkinson's disease (Barreto et al, 2014), sepsis (Zabrodskii et al, 2015), and IBD (Bai et al, 2007;Ruiz Castro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the administration route of nicotine in vivo models (i.e., oral administration, subcutaneous injection) plays a crucial role in the potential antiinflammatory effects of nicotine in intestinal inflammation (AlSharari et al, 2013) therefore we might have not been able to capture the full potential of nicotine with our model as nicotine dissemination through the blood stream, intestinal absorption, or gastrointestinal metabolism might play a crucial role in nicotine bioavailability and anti-inflammatory effects in the gut. Of note, other minor tobacco alkaloids, nAChR agonists as well, were also suggested as having potential antiinflammatory effects (Olsson et al, 1993;Bai et al, 2007;Alijevic et al, 2020;Ruiz Castro et al, 2020). Among these, the alkaloids anatabine and cotinine have displayed protective effects in animal models of inflammatory conditions, including Alzheimer's disease (Paris et al, 2011), Parkinson's disease (Barreto et al, 2014), sepsis (Zabrodskii et al, 2015), and IBD (Bai et al, 2007;Ruiz Castro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other minor tobacco alkaloids, nAChR agonists as well, were also suggested as having potential antiinflammatory effects (Olsson et al, 1993;Bai et al, 2007;Alijevic et al, 2020;Ruiz Castro et al, 2020). Among these, the alkaloids anatabine and cotinine have displayed protective effects in animal models of inflammatory conditions, including Alzheimer's disease (Paris et al, 2011), Parkinson's disease (Barreto et al, 2014), sepsis (Zabrodskii et al, 2015), and IBD (Bai et al, 2007;Ruiz Castro et al, 2020). Our results on anatabine are thus substantiated by the findings of previous studies that have demonstrated the anti-inflammatory effects of anatabine in in vivo disease models, indicating that this pyridine alkaloid might be a potential candidate for development of anti-inflammatory therapies (Paris et al, 2011;Paris et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine and all minor tobacco alkaloids have been shown to be pharmacologically active upon binding to several nicotinic acetylcholine receptors (nAChRs). Nicotine, anatabine, anabasine, anabaseine, and cotinine display protective effects in animal models of several inflammatory conditions, including sepsis, Parkinson's disease, Alzheimer's disease, and IBD [14]. Due to their amenability to both nuclear and plastid transformation, some Nicotiana species have been extensively used for metabolic engineering efforts based on classical transgenesis.…”
Section: Metabolic Engineering For the Production Of Biomass And High-value-added Metabolitesmentioning
confidence: 99%
“…Minor tobacco alkaloids are naturally occurring compounds [5] that are structurally [6] and functionally [7][8][9] analogous to nicotine, the primary psychoactive component in cigarettes, and have been the subject of research on novel therapeutics for smoking cessation [10], cognitive disorders including Alzheimer's disease [11][12][13] and Parkinson's disease [14], traumatic brain injury [15], inflammatory bowel disease [16] and psoriasis (Rock Creek Pharmaceuticals), as well as a novel strategy for pain management [17]. Previous research investigating the role of nicotine on body weight has repeatedly demonstrated that cigarette smoking and/or nicotine administration produces sustained weight loss and reduced food intake [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%